Connecting Reading & Writing in Second Language Writing Instruction - Hirvela, Alan (Book collections on Project MUSE., 2004)
"In Connecting Reading and Writing in Second Language Writing Instruction, Alan Hirvela contends that second language writing students should, first and foremost, be considered as readers, and he advocates the integration of reading and writing instruction with a thorough survey of theory, research, and pedagogy." "Connecting Reading and Writing in Second Language Writing Instruction will provide background knowledge on this issue of a reading and writing connection to ESL teachers in training, as well as to teachers who are already practicing."--Jacket